2012
DOI: 10.3109/03630269.2011.641135
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 26 bp Deletion [HBB: c.20_45del26bp] in Exon 1 of the β-Globin Gene Causing β-Thalassemia Major

Abstract: Molecular characterization of β-thalassemia (β-thal) is essential in prevention and in understanding the biology of the disease. Deletion mutations are relatively uncommon in β-thal. In this report, we describe a novel 26 bp deletion from codon 6 to codon 14 in the β-globin in a consanguineous family from Tamil Nadu, India. This novel mutation causes a shift in the normal reading frame of the β-globin coding sequence, and consequently, a premature chain termination of translation due to the creation of a stop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Functional evaluation of the gene modification in the ex vivo differentiated erythroid cells in the individual BMs as well as the CD34 + and CD235 + enriched BM pools through IEC identify that Crispr/Cas9-mediated disruption of codon 6 at exon 1 of HBB results in a reduction of HbA and an increase in HbF compared to the mock-edited cells (Figure 4A, 4C, S7A-D). The increase in HBF with RNP-mediated disruption could possibly be the result of re-capitulating naturally occurring deletional hereditary persistence of fetal hemoglobin (HPFH) phenotype that produces a beneficial functional outcome resulting in an increase in HbF 31, 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Functional evaluation of the gene modification in the ex vivo differentiated erythroid cells in the individual BMs as well as the CD34 + and CD235 + enriched BM pools through IEC identify that Crispr/Cas9-mediated disruption of codon 6 at exon 1 of HBB results in a reduction of HbA and an increase in HbF compared to the mock-edited cells (Figure 4A, 4C, S7A-D). The increase in HBF with RNP-mediated disruption could possibly be the result of re-capitulating naturally occurring deletional hereditary persistence of fetal hemoglobin (HPFH) phenotype that produces a beneficial functional outcome resulting in an increase in HbF 31, 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-eight mutations have been characterized, [34][35][36] but this number keeps increasing as more studies are reported. The regional distribution of mutations is also known.…”
Section: The Spectrum Of -Thalassemia Mutationsmentioning
confidence: 99%
“…4 Around sixty-eight mutations have been characterized. [5][6][7] But this number keeps on increasing as more studies are reported. 8 We run a screening program for detection of thalassaemia carriers.…”
Section: Introductionmentioning
confidence: 99%